Теоретико-игровой подход к задачам координации действий с обменом информации - Доценко, С.И. (Кибернетика и вычислительная техника, 2015)
Для кооперативной игры с ограниченной кооперацией рассмотрено коммуникативное расширение игры путем введения нового игрока, обязанностью которого является обеспечение координации взаимодействия между агентами исходной игры. Для расширенной игры применена методика вычисления вектора Шепли. Данный метод применен к биматричной игре «координация усилий» и игровой задаче оптимального выбора. Для кооперативної гри з обмеженою кооперацією розглянуто комунікативне розширення гри шляхом введення нового гравця, обов’язками якого є забезпечення координації взаємодії між агентами початкової гри. Для розширеної гри розглянуто методику обчислення вектора Шеплі. Даний метод було застосовано на прикладах біматричної гри «координація зусиль» та ігрової задачі оптимального вибору. Cooperative game theory is integral part of modern economics. The founder of this theory is Lloyd Shapley, who became Nobel prize winner in economics in 2012. In classical cooperative game theory the characteristic function of the game is rigidly defined and remains unchanged. The futher research are aimed at so-called extended games, when the extra players may be induced into the game. The extra players don’t participate in the game immediately, but they provide the connection between the origin players and so, may change the characteristic function of the game. For the extended game the Shapley values are calculated for origin and extra players equally well. Results. The Shapley values for extended communication games, based on both forces, coordination game and secretary problem are obtained in explicit form. As accessory result, the theorem on stochastic inequality for Shapley values in the case of player’s non-uniform joining times to coalition is proved and then illustrated by vivid example.